Advance Care Planning Protocols and Hospitalization Rates in Home Health Value-Based Purchasing. Issue 4 (November 2021) - Bigger, Sharon E.; Haddad, Lisa; Ahluwalia, Sangeeta C.; Glenn, Lee
Advance care planning is a conversation about personal values, future treatment choices, and designation of a surrogate decision-maker, that someone has in advance of a health crisis. Most existing studies on advance care planning have taken place outside of home health among populations with HIV/AIDS, cancer, dementia, and end stage renal disease. The U.S. home health population is living longer with chronic conditions such as pulmonary and cardiovascular illnesses, and hospitalization is a poor outcome. In 2016, Medicare implemented the Home Health Value-Based Purchasing Model, in which reimbursement rates for agencies in 9 regionally representative states were dependent on quantitative measures of quality performance. Part of the program was a process-level mandate requiring agencies to report on advance care planning. The aim of this study was to examine the relationship of home health advance care planning protocols with hospitalization rates. Descriptive and regression analyses were conducted on survey data of protocols and agency data of demographics and outcomes. Statistical significance was found in the positive correlation between advance care planning protocols and hospitalization. Recommendations are made for broadening the scope of evaluation of quality in home health to include goal-concordant care and transitions to appropriate services.